2011
DOI: 10.1093/imrn/rnr097
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Elements of Cosets of Small Subgroups and Applications

Abstract: We obtain a series of estimates on the number of small integers and small order Farey fractions which belong to a given coset of a subgroup of order t of the group of units of the residue ring modulo a prime p, in the case when t is small compared to p. We give two applications of these results: to the simultaneous distribution of two high degree monomials x k1 and x k2 modulo p and to a question of J. Holden and P. Moree on fixed points of the discrete logarithm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…So our goal is to find a "small" set Y ⊆ F * q such that its shifts cannot be inside of any coset of G e (we note that the value of r is unknown). Questions about the distribution of cosets of multiplicative groups have been considered in a number of works and have numerous applications, see [33] and also [6,8,12,9,11,39,41,42] for several more recent results and applications to cryptographic and computational number theory problems.…”
Section: Our Approachmentioning
confidence: 99%
“…So our goal is to find a "small" set Y ⊆ F * q such that its shifts cannot be inside of any coset of G e (we note that the value of r is unknown). Questions about the distribution of cosets of multiplicative groups have been considered in a number of works and have numerous applications, see [33] and also [6,8,12,9,11,39,41,42] for several more recent results and applications to cryptographic and computational number theory problems.…”
Section: Our Approachmentioning
confidence: 99%
“…The quantity N p,g (k) for k = 1, 2, 3 has recently been studied in [5,6,12,18,21,22,23,27,31]. Fixed points with various restrictions on u have been considered as well.…”
Section: Previously Known Resultsmentioning
confidence: 99%
“…A related conjecture by Holden and Moree [236] states that one should have F (p) = (1 + o (1))p. Bourgain et al [44] showed that F (p) = p + O(p 4/5+ǫ ) for a set of primes p of relative density 1 and in a later paper, [45],…”
Section: )mentioning
confidence: 97%